2022
DOI: 10.21511/ppm.20(1).2022.45
|View full text |Cite
|
Sign up to set email alerts
|

Trade openness and economic growth: Evidence from Azerbaijan

Abstract: A review of modern economic literature shows the lack of consensus on the relationship between the trade openness policy and the economic growth of countries. There is also an opinion that the policy of openness in emerging and resource-rich countries presents more opportunities for growth and development. Is this true, and under what conditions does openness lead to growth? Exploring the nature of trade openness and economic growth relationship in resource-rich emerging countries is the purpose of this paper.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Hence, the relationship between non-oil GDP growth and NPL rates in Azerbaijan should be further investigated. Previous research papers analyzing factors impacting non-oil GDP growth in Azerbaijan found a significant positive link between bank credits and non-oil GDP growth (Mukhtarov et al, 2019), a significant positive link between social expenditures of government and non-oil GDP growth, and a significant positive link in long-term between government expenditures and non-oil GDP growth , a significant positive link in the short-term between the trade openness and GDP growth (Seyfullayev, 2022), and no significant link between protectionist policies and non-oil GDP growth (Seyfullayev, 2020). Possible impacts of non-oil GDP and the stated factors impacting the dynamics of non-oil GDP on NPL rates in Azerbaijan should also be researched further.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 92%
“…Hence, the relationship between non-oil GDP growth and NPL rates in Azerbaijan should be further investigated. Previous research papers analyzing factors impacting non-oil GDP growth in Azerbaijan found a significant positive link between bank credits and non-oil GDP growth (Mukhtarov et al, 2019), a significant positive link between social expenditures of government and non-oil GDP growth, and a significant positive link in long-term between government expenditures and non-oil GDP growth , a significant positive link in the short-term between the trade openness and GDP growth (Seyfullayev, 2022), and no significant link between protectionist policies and non-oil GDP growth (Seyfullayev, 2020). Possible impacts of non-oil GDP and the stated factors impacting the dynamics of non-oil GDP on NPL rates in Azerbaijan should also be researched further.…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 92%
“…International trade plays a pivotal role in fostering extensive market integration and the globalization of trade activities among nations (Bashir et al, 2024;Dsouza et al, 2024;Nasim et al, 2023). This phenomenon exerts a positive impact on economic growth by facilitating the utilization of comparative advantages and the efficient allocation of resources (Sarkar, 2008;Keho, 2017;Ajayi and Araoye 2019;Klishch and Larionov 2022;Seyfullayev, 2022;. Such economic growth, in turn, contributes significantly to the overall improvement of human well-being (Kumari et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Over the decades, global trade, among other things, has been a key catalyst for economic growth, attracting the attention of academics across various trade-related growth investigations (Arvin et al, 2021;Yussif et al, 2022). Further, the integration of the world and pronounced trade openness has resulted in fundamental transformations in the economic environment, resulting in both possibilities and unforeseen threats to participating country growth (Seyfullayev, 2022). Due to the diversity of economic frameworks, technology, institutional infrastructures, and human capital, trade openness has long been a concern for many nations, particularly developing countries (Zahonogo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, trade openness promotes growth by enhancing job creation and domestic value added through its impact on investment, knowledge transfer, and competitiveness. Also, it promotes diversity in the opportunities and competencies to benefit from global trade openness and inclusion (Nguyen & Bui, 2021;Seyfullayev, 2022). Hence, a large corpus of empirical literature has been piloted to substantiate the benefits of international trade among countries and economic agents by investigating the dynamics as well as instituting causal linkages but with divergent outcomes (see Dollar & Kraay, 2004;Grossman & Helpman, 1990;Joshua et al, 2020;Keho, 2017;Ogede, 2014;Ozturk & Acaravci, 2010;Ulaşan, 2015).…”
Section: Introductionmentioning
confidence: 99%